Supporting higher degree research collaboration. (14th October 2019) - Gasson, Susan C.; Bruce, Christine
Abstract : Purpose: This paper aims to demonstrate the value of a collaborative research culture framework (Gasson and Bruce, 2018a), featuring trust and respect as core elements of healthy collaborations, to support the research success of higher degree research (HDR) students. HDR is a term used in Australia to reference Doctoral and Master by research programmes. Design/methodology/approach: The authors propose that by positioning collaboration as part of a research culture built on trust and respect, discussion about and the development of healthy collaborative research culture will be facilitated. A healthy culture is defined as one that supports sustainable and productive collaborative research. Findings: The applications of the framework demonstrate the role the framework can play in supporting researchers to understand, engage in and manage collaborations. Research limitations/implications: Reflection on discussions to date has led to the authors' view that collaborative success requires a unique set of skills (i.e. skills in the development of a collaborative research culture) and that the framework provides a deliberate and overt way of supporting development of those skills. Originality/value: The framework helps HDRs develop the capacity to build healthy collaborative research cultures vital for their research productivity and longer-term success as researchers.